Aortic valve neocuspidization with autologous pericardium in adult patients: UK experience and meta-analytic comparison with other aortic valve substitutes. (31st January 2021) - Benedetto, Umberto; Sinha, Shubhra; Dimagli, Arnaldo; Dixon, Lauren; Stoica, Serban; Cocomello, Lucia; Quarto, Cesare; Angelini, Gianni D; Dandekar, Uday; Caputo, Massimo
Abstract: OBJECTIVES: We sought to provide further evidence on the safety and efficacy of aortic valve neocuspidization (AVNeo) using autologous pericardium in adult patients with aortic valve disease by reporting clinical and echocardiographic results from the first UK experience and performing a meta-analytic comparison with other biological valve substitutes. METHODS: We reported clinical and echocardiographic outcomes of 55 patients (mean age 58 ± 15 years) undergoing AVNeo with autologous pericardium in 2 UK centres from 2018 to 2020. These results were included in a meta-analytic comparison between series on AVNeo (7 studies, 1205 patients, mean weighted follow-up 3.6 years) versus Trifecta (10 studies, 8705 patients, 3.8 years), Magna Ease (3 studies, 3137 patients, 4.1 years), Freedom Solo (4 studies, 1869 patients, 4.4 years), Freestyle (4 studies, 4307 patients, 7 years), Mitroflow (4 studies, 4760 patients, 4.1 years) and autograft aortic valve (7 papers, 3839 patients, 9.1 years). RESULTS: In the present series no patients required intraoperative conversion. After mean follow-up of 12.5 ± 0.9 months, 3 patients presented with endocarditis and 1 required reintervention. The remaining patients had absent or mild aortic valve insufficiency with very low peak and mean transvalvular gradients (16 ± 3.7 and 9 ± 2.2 mmHg, respectively). Meta-analytic estimates showed non-significant difference between AVNeo and all but Magna Ease valves with regards to structural valve degeneration, reintervention and endocarditis. When compared Magna Ease valve, AVNeo and other valve substitutes showed an excess of valve-related events. CONCLUSIONS: AVNeo is safe, associated with excellent haemodynamic profile. Its midterm risk of valve-related events is comparable to most biological valve substitutes. Magna Ease is potentially the best biological choice as far as risk of reintervention is concerned.